Tetrahedral copper(II) complexes with a labile coordination site supported by a tris-tetramethylguanidinato ligand - Shimizu, Ikuma; Faltermeier, Dieter; Kerscher, Marion; Comba, Peter (Inorganic chemistry, 2017)
A new tridentate N3 ligand (TMG3tach) consisting of cis,cis-1,3,5-triaminocyclohexane (tach) and three N,N,N′,N′-tetramethylguanidino (TMG) groups has been developed to prepare copper complexes with a tetrahedral geometry and a labile coordination site. Treatment of the ligand with CuIIX2 (X = Cl and Br) gave copper(II)-halide complexes, [CuII(TMG3tach)Cl]+ (2Cl) and [CuII(TMG3tach)Br]+ (2Br), the structures of which have been determined by X-ray crystallographic analysis. The complexes exhibit a four-coordinate structure with C3v symmetry, where the labile halide ligand (X) occupies a position on the trigonal axis. 2Br was converted to a methoxido-copper(II) complex [CuII(TMG3tach)(OMe)](OTf) (2OMe), also having a similar four-coordinate geometry, by treating it with an equimolar amount of tetrabutylammonium hydroxide in methanol. The methoxido-complex 2OMe was further converted to the corresponding phenolato-copper(II) (2OAr) and thiophenolato-copper(II) (2SAr) complexes by ligand exchange reactions with the neutral phenol and thiophenol derivatives, respectively. The electronic structures of the copper(II) complexes with different axial ligands are discussed on the basis of EPR spectroscopy and DFT calculations.